Capacity Building in Support of Security and Development (CBSD): securitising EU development policy? - Julian Bergmann (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Security sector reform (SSR) is a core element of the European Union's (EU) efforts to prevent violent conflicts and stabilise post-conflict situations. The existing legal framework excludes the use of EU budgetary sources to finance assistance to the armed forces of partner countries. Under the umbrella of Capacity Building in Support of Security and Development (CBSD), the EU seeks to address this funding gap and enable the financing of training, equipment and infrastructure to military actors. The main rationale behind CBSD is the assumption that security is a precondition for development, and that sustainable development can only be achieved when state institutions – including the military – acquire adequate capacities. To implement the CBSD initiative, the European Commission in July 2016 proposed to adapt the Regulation establishing the Instrument contributing to Stability and Peace (IcSP). The IcSP is the EU's main instrument to fund conflict prevention and peacebuilding activities. The Commission's proposal to amend the IcSP Regulation envisages the introduction of new types of assistance measures that address CBSD demands. Both EU institutions and the wider development community have controversially discussed the Commission's proposal. This Briefing Paper engages this debate and discusses the possible implications of the IcSP reform. The main argument of the paper is that the implementa¬tion of CBSD, as proposed by the European Commission, is likely to contribute to the securitisation of EU development policy. The provision of training and equipment to military actors is needed to preserve the EU's credibility and effectiveness as a security provider in countries such as Somalia and Mali. However, the use of the IcSP for funding CBSD activities sets a precedent for using development instruments within the EU's budget for financing assistance to military actors. Without a precise justification for the link between the proposed activities and EU development objectives, CBSD risks subordinating development policy to EU security goals. One key problem of the debate over CBSD is a lack of clarity concerning the scope of the envisaged assistance measures. Moreover, there is considerable uncertainty regarding EU development policy forming the legal basis of the Commission's proposal. Finally, civil society organisations fear that the proposed IcSP reform marks the beginning of a trend of shifting EU priorities from civilian to military instruments to address crises and violent conflicts. The main challenge is to address these concerns and find a suitable, permanent arrangement for funding CBSD activities within the EU's next Multiannual Financial Framework (MFF) between 2021 and 2027. In the short term, greater transparency of the envisaged CBSD activities and a substantive debate about their links to EU development policy objectives are needed. In the medium term, the EU should create a dedicated instrument that separates CBSD activities from funding for civilian conflict prevention and peacebuilding efforts.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Sicherheit; Frieden und fragile Staaten